أثر التدوير الوظيفي على الاحتراق الوظيفي في المؤسسة العمومية :دراسة حالة مؤسسة توزيع الكهرباء و الغاز-الأغواط - بن امبارك دلال; مراد فطوم; بعاج الهاشمي (جامعة عمار ثليجي -الأغواط, 2022)
This study sought to ascertain the extent to which functional recycling affects occupational combustion among the employees of the public institution - SONLGAZ - Agouat. The reality of the application of functional recycling policy in the public enterprise was highlighted. To achieve the objectives of the study, a random sample was adopted, which included the SONLGASE group of workers of different levels, consisting from 70 questionnaires. This study found that: Career rotation may be considered one of the most advanced and approved methods that gain employees new experience, skills and work development. Job rotation also contributes to reducing and reducing occupational combustion within the organization. Keywords: functional rotation, functional combustion, work stressors, sonelgas